EXPRESSION OF TOMATO PATHOGENESIS RELATED GENES IN RESPONSE TO TOBACCO MOSAIC VIRUS - A. Abdelkhalek (Journal of Animal and Plant Sciences, 2019)
Tobacco mosaic virus (TMV) causes severe damages and economic losses of tomato crop production and quality worldwide. In the current study, the nucleotide sequence with NCBI-BLAST and phylogenetic analysis for the movement protein gene revealed that the Egyptian TMV isolate (Acc# MG264131) exhibited 99% identity with that of a Slovenian isolate (Acc# KY810785). Moreover, the transcription profiles of PR1, PR2, PR3, PR5 and PR7 genes in TMV-infected tomato tissues were analysed using semi-quantitative RT-PCR technique. Compared to mock-inoculated plants, the statistical analysis revealed significant changes in the relative expression level of both PR2 and PR7 at the two intervals 6 and 15 days, post-inoculation with 32.3 and 34.7-fold change respectively. A significant change in transcription level of the two genes suggests that they play an essential role in the tomato defence system and could be disease-specific genes induced with the TMV infection. Based on the data obtained in this study and the previous studies, the down-regulation of PR2 and/or overexpression of PR7 in tomato plants could provide new insights in developing efficient strategies for reducing the tomato susceptibility to TMV infection.
Keywords: Tomato; TMV; Pathogen-related protein; RT-PCR